Optical absorption and fluorescence spectroscopy studies of Artepillin C, the major component of green propolis - Camuri, Isamara Julia; Costa, Adriano Batista; Ito, Amando Siuiti; Pazin, Wallance Moreira [UNESP] (Elsevier, 2018)
The bioactivity of propolis against several pathogens is well established, leading to the extensive consumption of that bee product to prevent diseases. Brazilian green propolis, collected by the species Apis mellifera, is one of the most consumed in the world. The chemical composition of green propolis is complex and it has been shown that it displays antioxidant, antimicrobial, anti-inflammatory and antitumor activities, especially due to the high content of Artepillin C. The molecule is a derivative of cinnamic acid with two prenylated groups, responsible for the improvement of the affinity of the compound for lipophilic environment. A carboxylic group (COOH) is also present in the molecule, making it a pH-sensitive compound and the pH-dependent structure of Artepillin C, may modulate its biological activity related to interactions with the cellular membrane of organisms and tissues. Molecular properties of Artepillin C on aqueous solution were examined by optical absorption, steady state and time-resolved fluorescence spectroscopies. Acid-base titration based on the spectral position of the near UV absorption band, resulted in the pKa value of 4.65 for the carboxylic group in Artepillin C. In acidic pH, below the pKa value, an absorption band raised around 350 nm at Artepillin C concentration above 50 μM, due to aggregation of the molecule. In neutral pH, with excitation at 310 nm, Artepillin C presents dual emission at 400 and 450 nm. In pH close to the pKa, the optical spectra show contribution from both protonated and deprotonated species. A three-exponential function was necessary to fit the intensity decays at the different pHs, dominated by a very short lifetime component, around 0.060 ns. The fast decay resulted in emission before fluorescence depolarization, and in values of fluorescence anisotropy higher than could be expected for monomeric forms of the compound. The results give fundamental knowledge about the protonation-deprotonation state of the molecule, that may be relevant in processes mediated by biological membranes.
Keywords: Aggregation properties; Artepillin C; Green propolis; Optical spectroscopy; pH effects